Public Policy Design and Decentralized Zakat Governance from the ABS–SBK Adat Perspective in Minangkabau - Jasri Waldi; Fatimah Setia Wardhani; Hospi Burda; Fitri Yenti (ZAWA: Management of Zakat and Waqf Journal, 2025)
This study examines a zakat governance model that aligns with the socio-cultural context of Minangkabau by integrating ABS–SBK values, traditional nagari institutions, and the state’s administrative framework. Although Indonesia’s zakat system is centralized and emphasizes formal accountability, this approach often fails to accommodate the strong social capital and adat-based deliberative traditions that characterize Minangkabau society. Through a literature review and analysis of documented ethnographic studies, the research identifies key mismatches between formal zakat mechanisms and nagari-based practices, particularly in terms of social legitimacy, the accuracy of mustahik identification, and the administrative capacity of local institutions. The findings indicate that nagari institutions possess cultural legitimacy and deep community knowledge, yet require state support to strengthen administrative procedures and reporting systems. Synthesizing governance, decentralization, ABS–SBK, and social capital theories, this study proposes a hybrid zakat governance model that includes formal recognition of nagari roles, establishment of Nagari Zakat Offices, coordination through Regional Zakat Forums, adaptive accountability, and digital transparency tools. This model is expected to enhance the effectiveness, legitimacy, and sustainability of zakat governance in Minangkabau